The effect of computer assisted language learning (call) on english language learners' pronunciation in secondary school in Pakistan - Farhat, Perveen Akhter (2019)
Pronunciation is a central component of speaking module in second language learning. However, it has always been neglected in the traditional second language learning classrooms. Mispronunciation impedes the communicative competence to a greater level. Pronunciation through computer-assisted language learning provides many advantages regarding improving phonemic sounds. The study aimed at evaluating the effectiveness of CALL to teach the segmental features of pronunciation: monophthongs, diphthongs and consonant sounds. An experimental study was designed in which 70 participants were selected from a public high school of Hasilpur Pakistan. The participants were divided into two groups: Experimental Group 1 and Experimental Group 2. A pronunciation test was utilized for pretest and posttest, consisting of 44 phonemic sounds. The duration of the treatment was six weeks in 46 sessions. Experimental Group 1 was taught phonemic sounds in a computer lab by showing phonetic videos and listening the different IPA sounds and symbols through Cambridge Advanced Learners’ Dictionary. Experimental Group 2 was taught the same material by teaching pronunciation without CALL. The mean scores of the pretests and posttests were analysed through SPSS using independent samples t-test to see the difference between the mean scores of both groups. The findings of the quantitative data showed that the group that received the treatment of phonetic videos and digital dictionary via computer performed better in learning the phonemic sounds than the group that received the treatment of pronunciation teaching without CALL. The current research is beneficial in promoting pronunciation teaching using CALL to address the segmental issues of pronunciation in Pakistan.